Teachers’ Digital information Literacy (DIL) competencies in teaching ICT-based projects: Malaysian secondary achools teachers’ experience / Salsuhaida Sulaiman ... [et al.] - Sulaiman, Salsuhaida; Shaifuddin, Norshila; Samsudin, Ahmad Zam Hariro; Yu, Halida (Faculty of Information Management, 2023)
In contrast to the fast growth of information and communication technologies (ICT) in 21st-century learning, digital information literacy (DIL) changed much. Even though there have been efforts to promote DIL, there is still a lack of knowledge about how it should be created and used in schools. Although understanding DIL competencies is a key skill for lifelong learning, it is still hard to teach. The primary objective of this study is to conduct a comprehensive review of recently published literature. The aim is to gain a nuanced understanding of the extent of knowledge possessed by teachers in select Malaysian secondary schools pertaining to the pedagogy of instructing ICT-based projects within the domain of design and technology, specifically denoted as "Reka Bentuk dan Teknologi" (RBT). The methodology employed for this study involves an exhaustive analysis of existing literature. Through a meticulous and systematic exploration of articles spanning diverse online databases, a curated selection of pertinent materials was identified and subsequently incorporated into the study. As the findings of this investigation emerged, a series of interrelated factors that interconnect ICT-based projects with the realm of DIL were discerned. These findings contribute to the broader understanding of how DIL can be synergistically integrated with the pedagogical ap- proach of RBT, shedding light on the strategies, challenges, and potential avenues for enhancing DIL competencies in the context of contemporary education. This study serves as a steppingstone towards bridging the gap between technological advancements and the development of essential digital literacy skills, fostering a more holistic and effective approach to education in the digital age.